أثـر القـراءات القـرآنيـة فـي الـدّرس النّـحوي - نعيم مزيد; مرجان روفائيل (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يقوم هذا البحث على دراسة القراءات القرآنية، وتوضيح أثرها في الدّرس النّحوي، وتضمَّن ـ أيضاً ـ الحديث عن الطّريقة التي تمَّ بها حفظ القرآن الكريم، وقراءاته بنوعيها المشهور والنادر، وبعد تعريفها تمَّت الإشارة إلى القراءة المقبولة وشروطها، وكذلك قرّائها، وللتعرُّف على القراءة الشاذة، استعرضت بعض آراء النّحاة حولها، وبيَّنت مدى اعتمادهم عليها في التّقعيد النّحوي، وعرض البحث ـ أيضاً ـ موضوع القراءات القرآنية والدرس النّحوي بعد أن تمَّ استعراض آراء عدد من نحاة البصرة والكوفة مثل: سيبويه، والأخفش الأوسط، والمبرّد من البصريّين، والكسائي والفرّاء وثعلب من الكوفيّين. وخُتِم البحث بالحديث عن علاقة القرآن والقراءات القرآنية بالإعراب، تجلَّى ذلك في خلال شواهد قرآنية تمَّ عرضها ومناقشتها؛ لتكون شاهداً ثرّاً على التلازم القائم بين القرآن والإعراب والفائدة المتحقّقة من ذلك على صعيد اللّغة والنّحو، وهل أدلّ على ذلك من كثرة المصنّفات في الإعراب القرآني ؟! This research work studies recitations of Al- Qoran and their influence on the analysis of syntax. It also explains the way to preserve Al-Qoran and its recitation in both the renown and rare ways. Following identification, we pointed out to the conditions of approved recitation, along with approved reciters, and the irregular recitation. Reviewing some of the syntax scholars’ ideas in this regards, we show the massive dependence on them in formulizing grammar rules. This research also discusses Al-Qoran recitation and grammar lesson, having reviewed opinions of same syntax scholars from (Busra) and (Kufa) of them are: (Sibaweh, Al akhfash, Al Awsat, Al Mubarrid), of the Busra school, and (Al kisai, Al farra, Thaalab) of the Kufa school. The study concludes with pointing to the relation of Al-Qoran and its recitations with syntax, which is shown through Al-Qoran’s evidence discussed to prove to the existing correspondence between Al-Qoran and syntax. The benefit of this relation concerning language and syntax is confirmed based on the multiple studies done in Al- Qoran syntax. .